2014
DOI: 10.3109/02770903.2014.892608
|View full text |Cite
|
Sign up to set email alerts
|

Improving preventive care in high risk children with asthma: lessons learned

Abstract: Objectives Rates of preventive asthma care after an asthma emergency department (ED) visit are low among inner-city children. The objective of this study was to test the efficacy of a clinician and caregiver feedback intervention (INT) on improving preventive asthma care following an asthma ED visit compared to an attention control group (CON). Methods Children with persistent asthma and recent asthma ED visits (N = 300) were enrolled and randomized into a feedback intervention or an attention control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…As previously reported, caregivers were primarily the biological mother (n=276, 92.3%) and single (n=210, 70.7%) (Authors, 2014b). A majority had completed high-school education/received their GED (n=117, 39.1%) or attended some college or trade school (n=81, 27.1%) (Table 1).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…As previously reported, caregivers were primarily the biological mother (n=276, 92.3%) and single (n=210, 70.7%) (Authors, 2014b). A majority had completed high-school education/received their GED (n=117, 39.1%) or attended some college or trade school (n=81, 27.1%) (Table 1).…”
Section: Resultssupporting
confidence: 59%
“…This sub-analysis is part of a larger randomized controlled trial that tested the effectiveness of a behavioral/educational intervention in families of children with poorly controlled asthma (Authros, 2012, 2014b). After obtaining institutional review board approval, caregivers of 300 inner-city children with asthma aged 3-10 years were recruited from two major urban hospitals after the child was discharged from a Pediatric ED.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8] Multiple quality improvement (QI) efforts to improve inpatient asthma care for children have been reported, but a positive impact on asthma outcomes is often not demonstrated. 3,[9][10][11][12][13][14][15][16][17][18] No data exist about the sustainability or long-term impact of QI interventions. Furthermore, most of the successful pediatric inpatient asthma interventions are implemented at a tertiary care pediatric centers, with little information available about dissemination to community hospitals.…”
mentioning
confidence: 99%
“…28 Other reports are limited to children and use only preprogram and postprogram comparisons. 36,[64][65][66][67][68][69][70][71][72][73] Ragazzi et al 36 were able to improve 4 of 8 care processes, but in exit interviews, staff reported those improvements were unlikely to be sustained without ongoing external support. Adding nurse managers, plus "intense interaction" with families and home visits, both Woods et al 72 and Lob et al 69 demonstrated a pre-to-post decrease in rates of asthma ED visits (68% and 70%, respectively), whereas Bunik et al 64 and Vernacchio et al 68 used similar methods but found no improved outcomes, with improvement only in documentation of care processes.…”
Section: Discussionmentioning
confidence: 99%